6a - (b - (3a - (2b + c + 4a - (a + 2b - c))))
6a - (b - (3a - (2b + c + 4a - a - 2b + c)))
6a - (b - (3a - (2b - 2b + 4a - a + c + c)))
6a - (b - (3a - (3a + 2c)))
6a - (b - (3a - 3a - 3c))
6a - (b - 3a + 3a + 3c)
6a - (b + 3c)
6a - b - 3c
x³ + x² - 25x - 25
x²(x) + x²(1) - 25(x) - 25(1)
x²(x + 1) - 25(x + 1)
(x² - 25)(x + 1)
(x² - 5x + 5x - 25)(x + 1)
(x(x) - x(5) + 5(x) - 5(5))(x + 1)
(x(x - 5) + 5(x - 5))(x + 1)
(x + 5)(x - 5)(x + 1)
36x² + 60x + 25
36x² + 30x + 30x + 25
6x(6x) + 6x(5) + 5(6x) + 5(5)
6x(6x + 5) + 5(6x + 5)
(6x + 5)(6x + 5)
(6x + 5)²
Answer:
z = 2.7x/r²y
Step-by-step explanation:
z = kx/r²y
½ = k × ⅓ ÷ (3² × ⅕)
½ = ⅓k × 5/9
k = 27/10 = 2.7
z = 27x/10r²y
z = 2.7x/r²y
Answer:
Step-by-step explanation:
The Egyptians calculated the area of a circle by a formula that gave the approximate value of 3.1605 for π. The first calculation of π was done by Archimedes of Syracuse (287–212 BC), one of the greatest mathematicians of the ancient world.
Do 14 times n which give you 14n. and divide by 3.
Answer: (14n)/3